2021
DOI: 10.51601/ijersc.v2i2.46
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Protection For Children Of Sexual Violence Victims In Indragirii Hilir Regency

Abstract: Currently, the phenomenon of children sexual abuse is a crime that is very distressing to society. It shows that children sexual abuse is an iceberg phenomenon that must be prevented so that children are no longer victims of sexual harassment by the responsible party. This research used normative legal as research methods. The data sources in the form of secondary data including primary, secondary and tertiary legal materials. Meanwhile, the data analysis used is in the form of qualitative analysis and deducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Saldanha et al (2018) posit that given the uncertain nature of the street environment, street children are obliged to always safeguard their properties from being stolen. In this research, the assertions of the street children suggest that the loss of belongings, such as money to theft was an unfavourable phenomenon, and this corroborates the findings of Wahyuni et al (2018), which indicated the incidence of theft as one of the unpleasant experiences for some street children. Some of the street children also indicated that they were deprived access to requisite needs, such as food and shelter.…”
Section: Discussionsupporting
confidence: 86%
“…Saldanha et al (2018) posit that given the uncertain nature of the street environment, street children are obliged to always safeguard their properties from being stolen. In this research, the assertions of the street children suggest that the loss of belongings, such as money to theft was an unfavourable phenomenon, and this corroborates the findings of Wahyuni et al (2018), which indicated the incidence of theft as one of the unpleasant experiences for some street children. Some of the street children also indicated that they were deprived access to requisite needs, such as food and shelter.…”
Section: Discussionsupporting
confidence: 86%
“…The testimony of a witness and/or victim is deemed sufficient to prove the criminal act of violence from the perpetrator accompanied by 1 (one) other valid evidence plus the judge's conviction.Further protection of witnesses and/or victims for reasons of health, security, safety and/or other valid reasons, cannot attend court, examination of them can be carried out by reading the minutes that have been given under oath/promise, through electronic recording and / or the examination is carried out directly over a distance using audiovisual communication tools with the strength of evidence considered the same as being present in court (Article 48). [22] (Aristi, Janitra, and Prihandini 2021) [23] (Luban 2015) ) [24] The proof of the crime of sexual violence which is only obtained from the testimony of a victim witness only, Article 25 paragraph (2) of the Law on the Crime of Sexual Violence provides a way, among which investigators can ask for information from the defendant's family as witnesses under oath/promise, without the consent of the defendant. The testimony of the witness, which was only obtained from the victim, did not take an oath/promise.…”
Section: Evidence In the Law On Sexual Violence In Indonesiamentioning
confidence: 99%
“…So that the development of evidence in the legislation on the crime of sexual violence, by including evidence as part of the evidence is the right progress in proving this crime in IndonesiaThe reality that we see now is that everything that affects the high crime of sexual violence against women and children in Indonesia in all aspects can be the cause (Purwanti and Zalianti 2018) [29]. The seriousness of the relevant parties, especially in the framework of handling victims of sexual crimes against women and children, needs to be socialized to the community and families in Indonesia to be willing to disclose sexual crimes that occur in society (Wahyuni, Irawan, and Rahmah 2021) [30 ]. So that the existence of evidence as part of the evidence in disclosing this sexual violence crime then also needs to be supported by good prevention efforts from every relevant party in Indonesia.…”
Section: Silent Evidencementioning
confidence: 99%
See 2 more Smart Citations